VD_FINDINFO HC / 2016 / 580 vom 21. April 2016 - VD Tribunal cantonal (2016)
DROIT DE PASSAGE, SERVITUDE, INDEMNITÉEN GÉNÉRAL, VOISIN, RESPONSABILITÉ DE DROIT PRIVÉ | 649 al. 1 CC, 649 al. 2 CC, 712h CC, 730 CC, 737 CC, 41 CO, 92 CPC